(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
Knowledge of phosphorus (P) uptake and its use efficiency by crop plants is essential for adequate management of the plant nutrients to sustain food production with a minimal environmental impact. To study the effects of P on the growth, leaf biomass production, P content and uptake and to estimate P use efficiency (PUE), minimum P requirement and critical leaf P content of stevia, a pot experiment was conducted in the net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University following completely randomized design (CRD) with three replications in acid and non-calcareous soils of Bangladesh. The applied treatments was six viz. 0 (P0), 25 (P25), 50 (P50), 75 (P75), 100 (P100) and 150 (P150) kg P ha-1. Plant samples were collected at 15 days interval to obtain different parameters. Collective results indicated that significantly highest values of different parameters were obtained with P @ 100 kg ha-1 and the lowest from P control. Phosphorus application increased leaf dry yield at harvest by 55 to 510% in acid soil and 70 to 488% in non-calcareous soil over control. The rapid growth of the plant was recorded at the later stages (30 to 60 days after planting). Phosphorus content and uptake was directly proportional with the increased levels of P except the treatment P150 in both soils. Maximum PUE and fertilizer P use efficiency (FPUE) was observed at P100 treatment. Critical P content was estimated to be ca 0.19 and 0.30% in the leaves of stevia plants grown in acid and non-calcareous soils, respectively. For maximum leaf biomass production of stevia grown in acid and non-calcareous soils, the minimum requirement of P was also estimated to be ca 109 and 104 kg ha-1, respectively. The information of this finding would contribute to optimize the soil P use and improve fertilizer management for stevia cultivation. Res. Agric., Livest. Fish.4(2): 55-68, August 2017